VD_FINDINFO HC / 2011 / 677 vom 18. November 2011 - VD Tribunal cantonal (2011)
EXPERT, INDEMNITÉEN GÉNÉRAL | 242 al. 1 CPC, 158 al. 1 CPC (CH), 158 al. 2 CPC (CH), 184 al. 3 CPC (CH), 91 al. 1 TFJC (2010), 91 al. 3 TFJC (2010)